The Caenorhabditis elegans Patched domain protein PTR-4 is required for proper organization of the precuticular apical extracellular matrix. Issue 3 (8th September 2021) - Cohen, Jennifer D; Cadena del Castillo, Carla E; Serra, Nicholas D; Kaech, Andres; Spang, Anne; Sundaram, Meera V
Abstract: The Patched-related superfamily of transmembrane proteins can transport lipids or other hydrophobic molecules across cell membranes. While the Hedgehog receptor Patched has been intensively studied, much less is known about the biological roles of other Patched-related family members. Caenorhabditis elegans has a large number of Patched-related proteins, despite lacking a canonical Hedgehog pathway. Here, we show that PTR-4 promotes the assembly of the precuticle apical extracellular matrix, a transient and molecularly distinct matrix that precedes and patterns the later collagenous cuticle or exoskeleton. ptr-4 mutants share many phenotypes with precuticle mutants, including defects in eggshell dissolution, tube shaping, alae (cuticle ridge) structure, molting, and cuticle barrier function. PTR-4 localizes to the apical side of a subset of outward-facing epithelia, in a cyclical manner that peaks when precuticle matrix is present. Finally, PTR-4 is required to limit the accumulation of the lipocalin LPR-3 and to properly localize the Zona Pellucida domain protein LET-653 within the precuticle. We propose that PTR-4 transports lipids or other hydrophobic components that help to organize the precuticle and that the cuticle and molting defects seen in ptr-4 mutants result at least in part from earlier disorganization of the precuticle.